Bacterial dynamin-like proteins reveal mechanism for membrane fusion - Marc Bramkamp (Nature Portfolio, 2018)
Abstract The dynamin superfamily of large GTPases comprises specialized members that catalyze fusion and fission of biological membranes. While fission-specific proteins such as dynamin work as homo-oligomeric complexes, many fusion catalysts such as mitofusins or bacterial dynamin-like proteins (DLPs) act as hetero-oligomers. However, so far it was unclear how these hetero-oligomeric DLPs assemble and how they function in membrane remodeling. The group of Harry Low report now on the structure of a DLP pair from Campylobacter jejuni, allowing detailed insight into the assembly mechanism and membrane tethering activity.